Qualidade do solo em unidades de manejo agroflorestal e mata nativa em neossolo flúvico no município de Irauçuba-CE - Nunes, Alessandro Antonio Lopes (2014)
The agroforestry systems constitute of techniques appropriated to local particularities, taking into account the coexistence with the semiarid. The objective of the researchwas evaluate the soil properties in agroforestry management units (SAFs), and native forest, in Bueno community, in the city of Irauçuba, CE. The treatments were: 1) Agroforestry management unit SAF 1, in the elevated portionof the landscape (interfluve); 2) Agroforestry management unit SAF 2, portion of slope (colluvium) and ; 3) native forest. Soil samples were collected, 5 samples being composed, derived of 15 sub-samples in areas of study, in the layers 0,0-0,10; 0,10-0,20; 0,20-0,30 e 0,30-0,40 m.The completely randomized design, with 5 repetitions, the treatments (SAF 1 , SAF 2 and native forest) and the portions the repetitions. Was applied to analysis of variance, the averages submitted to tukey test, in level of 5%.There were significant differences for the attributes analyzed, except to CEes, indicating low concentration of soluble salts, without risks of salinity (0,25 a 0,34 dS m-1). The exchangeable sodium (9,51 a 29,88 mg dm-3), with normal values of PST (0,66 a 1,35 %), in the SAF 2 differed from the others. The values of exchangeable sodium considered high, are not characterized with restriction a ccording to the normal EST . The units of SAF 1 and SAF 2 contributed to the maintenance of soil quality in top condition to MN. Featuring high levels of calcium, magnesium and potassium, with restrictions to the exchangeable sodium SAF 1 and SAF 2, in a lesser extentto the Native Forest